Willen weten wat wij niet weten kunnen. - Bruinsma, Max; Eijgenraam, Felix; Gortzak, Wouter; Hauser, Dick; Jonker, Pim; Roos, C.S.; Writs, Willem; van der Heijden, Chris (Amsterdam : Stichting Felix Meritis 1787-1987, 1987)
van Bennekom, Kors ; Boersma, Pieter ; Boonstra, Rommert ; van Bree, Johnnes Bernardus ; Greefkens, Leonie ; Huisman, Hetty ; Husly, Jacob Otten ; de Jonge, Jaap ; Kisman, Max ; Körmeling, John ; Mertens, Peter ; Polhuis, Gerard ; de Reus, Maarten ; Shaw, Jeffrey ; van Summeren, Ton ; van Tienhoven, Ronald ; Zegveld, Peter ; van Manen, Floris
Nederlands
boek